Barriers to the Developement of Collaborative Governance in Croatia - Klasinc, Jan (Socialiniai tyrimai, 2017)
This paper aims to establish whether collaborative governance may be a useful concept in Croatian local government and what barriers might prevent Croatian ULGs from developing such models. Recent research has shown that some ULGs in Croatia are more successful than others in terms of financial management and resource allocation, which may be due to better quality of civil servants working in local government and increased participation of citizens in public policy making but also to some form of collaborative governance. The second case also offers a possibility of achieving higher level of citizen satisfaction with local government on the basis of results, although this satisfaction is not necessarily linked to achieving proclaimed policy objectives or transparency and openness. In the case of e-governance we also assess the technological development of ULGs as a precondition for dynamic communication needed for collaboration. We find that in some cases the achievement of public good and community goals are due to better leadership and creating trust and in some others due to better participation in policies and involvement of citizens in common problems, such as unemployment. Barriers are detected by studying the most and least successful ULGs.